ALEKSANDRS LEMBERGS: CHOREOGRAPHIC ACHIEVEMENTS IN THE LIGHT OF HIS OWN MEMORIES AND EVIDENCES OF CONTEMPORARIES (Mūzikas akadēmijas raksti, 2024)
The creative period of Aleksandrs Lembergs (1921–1985) as choreographer (60’s–80’s of the 20th century) is marked by many magnificent ballet productions, popularity of Riga’s ballet in the world, search for innovative dance forms in the art of ballet, development of individual style of the young dancers, as well as involvement of foreign choreographers.